Effect Of Outward Foreign Direct Investment On Gross Domestic Product, Domestic Investment, And Unemployment In Indonesia - Gondo, Tutik Wiryanti (2022)
Gross Domestic Product (GDP) of Indonesia is growing but at relatively low rates if compared to the rates before the 1997 economic crisis. This could be explained by the low domestic investment which is only at its high recently but may be due to outward Foreign Direct Investment (OFDI). As part of the implication ofklow growth rate ofGDP and domestic investment in Indonesia, the unemployment rate is started to take off again recently, after a serious decline in the last decade. This suspects that the answer lies in the outward FDI. Hence, the key questions of this study are to investigate the effect of outward FDI on GDP, domestic investment, and unemployment in Indonesia. Since OFDI is not easy to handle as it is done by private firms, this study believes that several mitigating strategies of the potential adverse effect of OFDI should be designed, namely by inviting more inward foreign direct investment (IFDI), and promoting better education, and domestic financial development. This study tries to confirm their importance by setting them as another three objectives of this study. Utilizing data of Indonesia spanning from 1980 till 2018 by using vector error correction model approach, this study confirms that OFDI has a negative impact on GDP, investment, and unemployment in Indonesia.